Towards Optimizing the Quality of Long-Term Physiological Signals Monitoring by Using Anhydrous Carbon Paste Electrode - Wang, Xin; Tian, Qiong; Zhu, Mingxing; Wang, Yingying; Wang, Boya; Jing, Xiaobei; Yokoi, Hiroshi; Li, Lin; Liu, Zhenzhen; Huang, Weimin; Chen, Shixiong; Liu, Zhiyuan; et al. (IEEE Transactions on Biomedical Engineering, 2023)
Long-term physiological signal monitoring is very important for the diagnosis of health conditions that occur randomly and cannot be easily detected by a short period of a hospital visit. However, the conventional wet electrodes suffered from the problem of signal quality degradation due to the gradual dehydration of the conductive gel. An anhydrous carbon paste electrode (CPE) constructed by a composite of carbon black and polydimethylsiloxane was proposed to enable long-term physiological signal monitoring without signal quality degradation as time elapses. The performance was systematically compared with conventional electrodes when measuring long-term physiological signals including electrocardiogram (ECG), electromyogram (EMG), electroencephalogram (EEG) and auditory brainstem response (ABR). The proposed CPE showed more stable skin-electrode impedance and higher signal qualities as the monitoring time increased up to 48 days, with signal-to-noise ratios (SNRs) of 16.43 ± 10.39 dB higher for ECG and 24.30 ± 7.79 dB higher for EMG when compared with wet electrodes. The CPE method could also obtain more consistent ABR waveform morphologies and could measure EEG under sweating conditions. It is believed that the proposed CPE could be a potential candidate for durable and robust wearable sensors systems on long-term physiological signal monitoring.